Successfully promoting decentralisation: the potential of the multi-stakeholder approach - Lisa Groß (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
Sustainable Development Goal 17 assigns an important role to multi-stakeholder approaches in achieving the Sustainable Development Goals (SDGs). What are the advantages and impacts of a multi-stakeholder approach in decentralisation programmes? The multi-stakeholder approach aims to involve all stakeholders from politics, civil society and the private sector that are relevant for a reform process. In the context of decentralisation programmes, this approach usually allows for simultaneous cooperation with political actors (supply side) and civil society (demand side) and applies to all state levels (i.e. national, regional and local). There have been few studies until now on how a multi-stakeholder approach can contribute to the success of decentralisation and how it can develop its full potential. This paper argues that the multi-stakeholder approach supports the effectiveness as well as the sustainability of decentralisa¬tion. Important is the horizontal as well as vertical cooperation in the multi-level system when promoting decentralisation: Simultaneously strengthening the supply and demand side increases the effectiveness of decentralisation reforms. The example of citizen participation shows that support to local authorities makes it easier for civil society to gain access, while support to civil society enables it to participate more effectively. By strengthening citizen participation in this way, citizen participation is more likely to lead to the improvement of municipal services. If cooperation takes place in a multi-level system, decentralisation can be promoted in a more sustainable manner: for example, international actors – together with civil society – can bring experiences from the local level into legislation and subsequently support its implementation at the local level. To fully exploit the potential of the multi-stakeholder approach, the following is important: International actors should find a balance in supporting state and non-state actors in decentralisa¬tion processes. The (non-governmental) demand side often receives less attention. Supporting different actors is not about an `either-or' situation but rather an `as well as'. Citizen participation should lead to visible results so that the willingness to participate in civil society is established in the long term. This is why the follow-up of citizen participation on both the supply and demand side is important. Continuity and intensity of support are important for the sustainable success of the reforms. The results stem from a research project of the German Development Institute on the impact assessment of governance programmes.
Keywords: 330; Governance; Wirksamkeit und Evaluierung